Identification of residues in the first transmembrane domain of the P2X7 that regulates receptor trafficking, sensitization, and dye uptake function - Rupert, Marian; Bhattacharya, Anirban; Sivcev, Sonja; Knezu, Michal; Cimicka, Jana; Zemkova, Hana (Journal of neurochemistry, 2023)
P2X receptors (P2X1-7) are trimeric ion channels activated by extracellular ATP. Each P2X subunit contains two transmembrane helices (TM1 and TM2). We substituted all residues in TM1 of rat P2X7 with alanine or leucine one by one, expressed mutants in HEK293T cells, and examined the pore permeability by recording both membrane currents and fluorescent dye uptake in response to agonist application. Alanine substitution of G27, K30, H34, Y40, F43, L45, M46, and D48 inhibited agonist-stimulated membrane current and dye uptake, and all but one substitution, D48A, prevented surface expression. Mutation V41A partially reduced both membrane current and dye uptake, while W31A and A44L showed reduced dye uptake not accompanied by reduced membrane current. Mutations T28A, I29A, and L33A showed small changes in agonist sensitivity, but they had no or small impact on dye uptake function. Replacing charged residues with residues of the same charge (K30R, H34K, and D48E) rescued receptor function, while replacement with residues of opposite charge inhibited (K30E and H34E) or potentiated (D48K) receptor function. Prolonged stimulation with agonist-induced current facilitation and a leftward shift in the dose-response curve in the P2X7 wild-type and most functional mutants, but sensitization was absent in the W31A, L33A, and A44L. Detailed analysis of the decay of responses revealed two kinetically distinct mechanisms of P2X7 deactivation: fast represents agonist unbinding, and slow might represent resetting of the receptor to the resting closed state. These results indicate that conserved and receptor-specific TM1 residues control surface expression of the P2X7 protein, non-polar residues control receptor sensitization, and D48 regulates intrinsic channel properties.
Keywords: Animals; Ion Channels; HEK293 Cells; biologický transport; Receptors, Purinergic P2X7; purinergní receptory P2X7; Rats; Protein Domains; mutace; proteinové domény; Biological Transport; Humans; HEK293 buňky; adenosintrifosfát; Adenosine Triphosphate; lidé; zvířata; Mutation; krysa rodu Rattus; iontové kanály